A cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric and preparation method thereof
By using cross-sectional modified polyester fiber and cotton fiber blending and a variety of chemical treatment technologies in moisture-absorbing and quick-drying fabrics, the shortcomings of existing fabrics in flame retardant, antistatic and wear resistance are solved, and a higher performance functional fabric is achieved.
Patent Information
- Application Number
- CN202411570411.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing moisture-absorbing and fast-drying fabrics still have room for improvement in flame retardant, antistatic and wear resistance.
Modified polyester fibers with cross-sections are blended with cotton fibers, and the hydrophilic, antibacterial and flame retardant properties of the fabric are enhanced by plasma treatment, epoxy chlorohydrin cross-linking and chemical grafting technology of modified carbon nanotubes. At the same time, the fiber binding strength and wear resistance are improved through blocked isocyanate cross-linking agents.
It significantly improves the fabric's anti-permeability, antistatic properties, antibacterial properties and flame retardant properties, while enhancing the wear resistance of the fabric, which is suitable for high-performance clothing.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile fabrics, and in particular to a cross-shaped anti-permeability, moisture-absorbing and quick-drying functional fabric and a preparation method thereof. Background Art
[0002] People often get their clothes soaked after sweating during exercise, which makes people feel unsightly, especially in hot and humid summer. Especially after the human body has done a lot of exercise, the clothes will quickly get soaked and cannot dry quickly. They will stick to the body and are very uncomfortable. It is also easy to breed bacteria when worn for a long time.
[0003] It is under such environmental conditions that cross polyester came into being. The cross section of cross polyester fiber is cross-shaped, which can improve the gloss effect of the fiber. At the same time, cross polyester has four grooves, and uses the moisture-conducting structure to achieve the drainage effect. It can quickly absorb moisture and sweat from the skin surface and discharge them to the outer layer for evaporation, so that the body remains dry and comfortable, and can regulate body temperature. It also has the characteristics of core absorption, breathability, quick drying, no sticking discomfort, easy to get wet, and easy to handle. However, due to the regular macromolecular chain of polyester fiber, no hydrophilic groups, and smooth fiber surface, the ability of its fabric to pass through the skin to excrete high-heat sweat, that is, poor moisture permeability, it is easy to accumulate static electricity on the fiber and cause pilling.
[0004] Chinese patent document CN114474890A discloses a moisture-absorbing and quick-drying fabric and its preparation method, wherein Ula grass fiber and cotton fiber are blended to obtain blended yarn, and then a hydrophilic inner layer is obtained by weaving; special-shaped polyester fiber is blended to form an intermediate layer by weaving; modified cellulose fiber is blended with cotton fiber and special-shaped polyester fiber to obtain composite yarn, and then the outer layer is obtained by warp and weft weaving; the outer layer is immersed in a moisture-absorbing and quick-drying finishing liquid, and then immersed and rolled twice to obtain a pretreated outer layer; the hydrophilic inner layer, the intermediate layer and the pretreated outer layer are compounded by bonding, and then dried and baked to obtain a moisture-absorbing and quick-drying fabric. The moisture-absorbing and quick-drying fabric prepared by the invention has obvious moisture-absorbing and quick-drying effect, the fabric has certain anti-yellowing performance and antibacterial performance, and the preparation method is simple, the preparation process is easy to operate, and it is suitable for industrial production; although the invention obtains a moisture-absorbing and quick-drying fabric by blending, its flame retardant, antistatic and wear resistance properties still need to be improved. Summary of the invention
[0005] The main purpose of the invention is to provide a cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric with good comprehensive performance and a preparation method thereof.
[0006] To achieve the above object, the present invention provides a method for preparing a cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric, comprising the following steps:
[0007] S1, dispersing the polyester fiber treated with plasma in water, adding epichlorohydrin and carboxymethyl chitosan thereto, heating and stirring to react, after the reaction is completed, filtering, washing, and drying the reaction product, and then spraying it through a cross-shaped spinneret, and then stretching and winding it to spin a cross-section modified polyester fiber;
[0008] S2, blending the cross-section modified polyester fiber and cotton fiber to form warp yarn and weft yarn, and then cross-weaving the warp yarn and weft yarn to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth;
[0009] S3, immersing the cross-shaped anti-permeability moisture absorption and quick-drying functional fabric base fabric in the finishing liquid for padding treatment, and then baking, washing and drying the fabric base fabric after the padding treatment to obtain the cross-shaped anti-permeability moisture absorption and quick-drying functional fabric.
[0010] Preferably, the plasma treatment conditions in step S1 are as follows: oxygen is introduced into the plasma instrument after evacuation, the power is set to 150-200 W, and the treatment time is 5-10 min.
[0011] Preferably, in step S1, the mass ratio of polyester fiber, epichlorohydrin and carboxymethyl chitosan is 10-20:2-3:4-8.
[0012] Preferably, in step S2, in the composition of the warp yarn, the content of the cross-section modified polyester fiber is 50-60wt%, and the content of the cotton fiber is 40-50wt%; in the composition of the weft yarn, the content of the cross-section modified polyester fiber is 70-80wt%, and the content of the cotton fiber is 20-30wt%.
[0013] Further preferably, in step S2, the linear density of the warp yarn is 15-20tex, and the linear density of the weft yarn is 15-20tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven with each other one above and one below to form a plain weave, the warp yarn density is 360-365 yarns / 10cm, and the weft yarn density is 325-330 yarns / 10cm.
[0014] Preferably, the dipping and rolling process in step S3 is double dipping and double rolling, with a liquid carrying rate of 70-95%.
[0015] Preferably, the baking conditions in step S3 are pre-baking at 90-100° C. for 2-3 min, then cooling to 60-70° C., and continuing baking for 2-4 min.
[0016] Preferably, the finishing liquid in step S3 is obtained by uniformly mixing 1-2 parts of modified carbon nanotubes, 4-8 parts of blocked isocyanate crosslinking agent, 0.5-1 part of hydroxyethyl cellulose, and 80-120 parts of water.
[0017] Preferably, the preparation method of the modified carbon nanotubes is as follows:
[0018] The carbon nanotubes are dispersed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, heated and stirred after ultrasonic treatment, cooled to room temperature, filtered, the solids are collected, washed with water until neutral, and dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes are evenly mixed with an ethanol aqueous solution, 3-aminopropyltriethoxysilane is added, heated for reaction, cooled, filtered and dried to obtain amino carbon nanotubes; the amino carbon nanotubes, epichlorohydrin, melamine and sulfaguanidine are added to water, stirred and mixed evenly, sodium hydroxide is added, heated and stirred for reaction, after the reaction is completed, filtered, the solids are collected and dried to obtain modified carbon nanotubes.
[0019] Preferably, the mass ratio of the pretreated carbon nanotubes to 3-aminopropyltriethoxysilane is 6-10:1-2.
[0020] Preferably, the mass ratio of the amino carbon nanotubes, epichlorohydrin, melamine and sulfaguanidine is 5-6:3-5:4-6:2-3.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses cross-section modified polyester fiber and cotton fiber for blending, which can simultaneously give the fabric skin-friendly, hygroscopic and quick-drying properties; wherein the cross-section modified polyester fiber can form a special microstructure, effectively blocking the penetration of light, moisture and wind, forming an effective barrier, and enhancing the anti-permeability performance of the fabric;
[0023] 2. The present invention uses plasma to treat polyester fibers, which can form micropores and slits on the fiber surface, provide more physical anchoring points, and activate the polyester fiber surface, introducing active groups such as carboxyl and hydroxyl groups on the surface; carboxymethyl chitosan is introduced into the polyester fiber through the cross-linking effect of epichlorohydrin, thereby improving the hydrophilicity and skin affinity of the cross-section polyester fiber, which is beneficial to improving the moisture absorption, quick-drying and antibacterial properties of the fabric;
[0024] 3. The present invention activates carbon nanotubes with concentrated sulfuric acid and concentrated nitric acid, then introduces amino groups into the carbon nanotubes, and then grafts melamine and sulfaguanidine onto the carbon nanotubes by chemical grafting under the action of epichlorohydrin, thereby improving the dispersion of carbon nanotubes in fabrics, and by grafting hydrophilic melamine and sulfaguanidine onto the carbon nanotubes, the hygroscopicity of the fabric is enhanced, the accumulation of charges on the fabric is reduced, and the pilling of the fiber surface of the cross-section polyester fiber due to static electricity accumulation during use is prevented, thereby improving the antistatic performance of the fabric; the carbon nanotubes, melamine and sulfaguanidine also have antibacterial and flame retardant properties, and are introduced into the composite fabric, and the three synergistically enhance the antibacterial and flame retardant properties of the fabric.
[0025] 4. The finishing liquid of the present invention contains a blocked isocyanate cross-linking agent. During the baking process, the blocked isocyanate cross-linking agent releases -NCO groups and undergoes cross-linking reactions with the hydroxyl groups and amino groups on the cross-section polyester fibers and cotton fibers, thereby improving the bonding strength between the cross-section polyester fibers and the cotton fibers, increasing the friction between the fibers, making it more difficult for the fibers to slide relative to each other, thereby improving the wear resistance of the functional fabric, and enabling the modified carbon nanotubes to be firmly attached to the fabric. After multiple washings, the fabric still has good antibacterial and flame retardant properties. DETAILED DESCRIPTION
[0026] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0027] Some of the raw materials of the present invention come from the following sources:
[0028] Carboxymethyl chitosan, viscosity ≤100 MPa·s, was purchased from Hubei Xingyan New Materials Technology Co., Ltd.
[0029] Carbon nanotubes, single arm, diameter 10-30 nm, short tube length 1-2 μm, long tube length 5-20 μm, purchased from Guangzhou Hongwu Material Technology Co., Ltd.
[0030] Blocked isocyanate crosslinking agent, model C66, was purchased from Guangzhou Wanjun Chemical Technology Co., Ltd.
[0031] Example 1
[0032] A method for preparing a cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric comprises the following steps:
[0033] S1. Disperse 150 parts of polyester fibers in 500 mL of water after plasma treatment. The plasma treatment process is to evacuate the plasma instrument and then introduce oxygen. The power is set to 180 W and the treatment time is 8 min. Add 24.8 g of epichlorohydrin and 58.6 g of carboxymethyl chitosan, heat and stir at 60 ° C for 2 h, and after the reaction is completed, filter, wash and dry the reaction product, and then spray it through a cross-shaped spinneret, and then stretch and wind it to obtain a cross-section modified polyester fiber.
[0034] S2. Cross-section modified polyester fiber and cotton fiber are blended to form warp yarn and weft yarn, wherein the content of cross-section modified polyester fiber in the warp yarn is 55wt%, and the content of cotton fiber is 45wt%; the content of cross-section modified polyester fiber in the weft yarn is 76wt%, and the content of cotton fiber is 24wt%; then the warp yarn and the weft yarn are cross-woven to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth; the linear density of the warp yarn is 18tex, and the linear density of the weft yarn is 18tex. The specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 362 yarns / 10cm, and the weft yarn density is 328 yarns / 10cm;
[0035] S3. The cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric base fabric is immersed in the finishing liquid for double immersion and double rolling treatment, and the liquid carrying rate is 80%. Then, the fabric base fabric after the immersion and rolling treatment is baked, washed, and dried to obtain the cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric; the baking conditions are pre-baking at 95°C for 3 minutes, then cooling to 65°C, and continuing to bake for 3 minutes; the finishing liquid is obtained by uniformly mixing 15g of modified carbon nanotubes, 68g of blocked isocyanate cross-linking agent, 7g of hydroxyethyl cellulose, and 1000g of water.
[0036] The preparation method of the modified carbon nanotubes is as follows:
[0037] 8g of carbon nanotubes were dispersed in a mixed acid solution of 100ml of concentrated sulfuric acid and 50ml of concentrated nitric acid, and after ultrasonic treatment for 30min, the mixture was stirred at 80℃ for 4h, cooled to room temperature, filtered, washed with water until neutral, and dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes were mixed evenly with 100mL of 50wt% ethanol aqueous solution, 1.5g of 3-aminopropyltriethoxysilane was added, and the mixture was heated at 50℃ for 2h, cooled, filtered, and dried to obtain amino carbon nanotubes; 5.5g of amino carbon nanotubes, 4g of epichlorohydrin, 5g of sulfaguanidine, and 2.5g of melamine were added to 100mL of water, stirred and mixed evenly, the pH value was adjusted to 9 with 1mol / L sodium hydroxide aqueous solution, heated and stirred at 60℃ for 4h, and after the reaction was completed, the solid was filtered and collected, and the solid was washed with water until the filtrate was neutral and then dried to obtain modified carbon nanotubes.
[0038] Example 2
[0039] A method for preparing a cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric comprises the following steps:
[0040] S1. 100 g of polyester fiber was dispersed in 500 mL of water after being treated with plasma. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen. The power was set to 200 W and the treatment time was 5 min. 20.2 g of epichlorohydrin and 40 g of carboxymethyl chitosan were added thereto. The mixture was heated and stirred at 60 ° C for 2 h. After the reaction was completed, the reaction product was filtered, washed, and dried. The product was then ejected from a cross-shaped spinneret and then stretched and wound to obtain a cross-section modified polyester fiber.
[0041] S2. Cross-section modified polyester fiber and cotton fiber are blended to form warp yarn and weft yarn, wherein the warp yarn contains 50wt% of cross-section modified polyester fiber and 50wt% of cotton fiber; the weft yarn contains 70wt% of cross-section modified polyester fiber and 30wt% of cotton fiber; the warp yarn and the weft yarn are cross-woven to obtain a cross-proof moisture-absorbing and quick-drying functional fabric base cloth; the linear density of the warp yarn is 15ex, and the linear density of the weft yarn is 15tex. The specific weaving process is: the warp yarn and the weft yarn are interwoven one above the other to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm;
[0042] S3. The cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric base fabric is immersed in the finishing liquid for double immersion and double rolling treatment, and the liquid carrying rate is 70%. Then, the fabric base fabric after the immersion and rolling treatment is baked, washed, and dried to obtain the cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric; the baking conditions are pre-baking at 90°C for 2min, then cooling to 60°C, and continuing to bake for 2min; the finishing liquid is obtained by uniformly mixing 10g of modified carbon nanotubes, 40g of blocked isocyanate cross-linking agent, 0.5g of hydroxyethyl cellulose, and 800g of water.
[0043] The preparation method of the modified carbon nanotubes is as follows:
[0044] 6 g of carbon nanotubes were dispersed in a mixed acid solution of 100 ml of concentrated sulfuric acid and 50 ml of concentrated nitric acid, and after ultrasonic treatment for 30 min, the mixture was stirred at 80 ° C for 4 h, cooled to room temperature, filtered, washed with water until neutral, and dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes were mixed evenly with 100 mL of 50 wt% ethanol aqueous solution, 1.1 g of 3-aminopropyltriethoxysilane was added, and the mixture was heated at 50 ° C for 2 h, cooled, filtered, and dried to obtain amino carbon nanotubes; 5 g of amino carbon nanotubes, 3 g of epichlorohydrin, 4 g of sulfaguanidine, and 2 g of melamine were added to 100 mL of water, stirred and mixed evenly, the pH value was adjusted to 10 with 1 mol / L sodium hydroxide aqueous solution, heated and stirred at 60 ° C for 4 h, and after the reaction was completed, filtered, the solid matter was collected, and the solid matter was washed with water until the filtrate was neutral and then dried to obtain modified carbon nanotubes.
[0045] Example 3
[0046] A method for preparing a cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric comprises the following steps:
[0047] S1. 200 g of polyester fiber was dispersed in 500 mL of water after being treated with plasma. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen. The power was set to 150 W and the treatment time was 10 min. 29.8 g of epichlorohydrin and 78.5 g of carboxymethyl chitosan were added thereto. The mixture was heated and stirred at 60 ° C for 2 h. After the reaction was completed, the reaction product was filtered, washed, and dried. After being ejected from a cross-shaped spinneret, it was stretched and wound to obtain a cross-section modified polyester fiber.
[0048] S2. Cross-section modified polyester fiber and cotton fiber are blended to form warp yarn and weft yarn, wherein the warp yarn has a content of 60wt% of cross-section modified polyester fiber and a content of 40wt% of cotton fiber; the weft yarn has a content of 80wt% of cross-section modified polyester fiber and a content of 20wt% of cotton fiber; and the warp yarn and the weft yarn are cross-woven to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth; the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 20tex. The specific weaving process is: the warp yarn and the weft yarn are interwoven one above the other to form a plain weave, the warp yarn density is 365 yarns / 10cm, and the weft yarn density is 330 yarns / 10cm;
[0049] S3. The cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric base fabric is immersed in the finishing liquid for double immersion and double rolling treatment, and the liquid carrying rate is 95%. Then, the fabric base fabric after the immersion and rolling treatment is baked, washed, and dried to obtain the cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric; the baking conditions are pre-baking at 100°C for 2 minutes, then cooling to 70°C, and continuing to bake for 2 minutes; the finishing liquid is obtained by uniformly mixing 20g of modified carbon nanotubes, 80g of blocked isocyanate cross-linking agent, 10g of hydroxyethyl cellulose, and 1200g of water.
[0050] The preparation method of the modified carbon nanotubes is as follows:
[0051] 10g of carbon nanotubes were dispersed in a mixed acid solution of 100ml of concentrated sulfuric acid and 50ml of concentrated nitric acid, and after ultrasonic treatment for 30min, the mixture was stirred at 80℃ for 4h, cooled to room temperature, filtered, washed with water until neutral, and dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes were mixed evenly with 100mL of 50wt% ethanol aqueous solution, 2g of 3-aminopropyltriethoxysilane was added, heated at 50℃ for reaction for 2h, cooled, filtered and dried to obtain amino carbon nanotubes; 6g of amino carbon nanotubes, 5g of epichlorohydrin, 6g of sulfaguanidine, and 3g of melamine were added to 100mL of water, stirred and mixed evenly, the pH value was adjusted to 11 with 1mol / L sodium hydroxide aqueous solution, heated and stirred at 60℃ for reaction for 4h, and after the reaction was completed, filtered, the solid matter was collected, and the solid matter was washed with water until the filtrate was neutral and then dried to obtain modified carbon nanotubes.
[0052] Comparative Example 1
[0053] A method for preparing a cross-shaped anti-permeability, moisture-absorbing and quick-drying functional fabric is similar to that of Example 1, except that the polyester fiber is not grafted with carboxymethyl chitosan, and specifically comprises the following steps:
[0054] S1. 150 parts of polyester fibers were dispersed in 500 mL of water after being treated with plasma. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen. The power was set to 180 W and the treatment time was 8 min. Then, the fibers were ejected from a cross-shaped spinneret and stretched and wound to obtain cross-section modified polyester fibers.
[0055] S2. Cross-section modified polyester fiber and cotton fiber are blended to form warp yarn and weft yarn, wherein the content of cross-section modified polyester fiber in the warp yarn is 55wt%, and the content of cotton fiber is 45wt%; the content of cross-section modified polyester fiber in the weft yarn is 76wt%, and the content of cotton fiber is 24wt%; then the warp yarn and the weft yarn are cross-woven to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth; the linear density of the warp yarn is 18tex, and the linear density of the weft yarn is 18tex. The specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 362 yarns / 10cm, and the weft yarn density is 328 yarns / 10cm;
[0056] S3. The cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric base fabric is immersed in the finishing liquid for double immersion and double rolling treatment, and the liquid carrying rate is 80%. Then, the fabric base fabric after the immersion and rolling treatment is baked, washed, and dried to obtain the cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric; the baking conditions are pre-baking at 95°C for 3 minutes, then cooling to 65°C, and continuing to bake for 3 minutes; the finishing liquid is obtained by uniformly mixing 15g of modified carbon nanotubes, 68g of blocked isocyanate cross-linking agent, 7g of hydroxyethyl cellulose, and 1000g of water.
[0057] The preparation method of the modified carbon nanotubes is as follows:
[0058] 8g of carbon nanotubes were dispersed in a mixed acid solution of 100ml of concentrated sulfuric acid and 50ml of concentrated nitric acid, and after ultrasonic treatment for 30min, the mixture was stirred at 80℃ for 4h, cooled to room temperature, filtered, washed with water until neutral, and dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes were mixed evenly with 100mL of 50wt% ethanol aqueous solution, 1.5g of 3-aminopropyltriethoxysilane was added, and the mixture was heated at 50℃ for 2h, cooled, filtered, and dried to obtain amino carbon nanotubes; 5.5g of amino carbon nanotubes, 4g of epichlorohydrin, 5g of sulfaguanidine, and 2.5g of melamine were added to 100mL of water, stirred and mixed evenly, the pH value was adjusted to 9 with 1mol / L sodium hydroxide aqueous solution, heated and stirred at 60℃ for 4h, and after the reaction was completed, the solid was filtered and collected, and the solid was washed with water until the filtrate was neutral and then dried to obtain modified carbon nanotubes.
[0059] Comparative Example 2
[0060] A method for preparing a cross-shaped anti-permeability, moisture-absorbing and quick-drying functional fabric is similar to that of Example 1, except that carbon nanotubes are added to the finishing liquid, and specifically comprises the following steps:
[0061] S1. Disperse 150 parts of polyester fibers in 500 mL of water after plasma treatment. The plasma treatment process is to evacuate the plasma instrument and then introduce oxygen. The power is set to 180 W and the treatment time is 8 min. Add 24.8 g of epichlorohydrin and 58.6 g of carboxymethyl chitosan, heat and stir at 60 ° C for 2 h, and after the reaction is completed, filter, wash and dry the reaction product, and then spray it through a cross-shaped spinneret, and then stretch and wind it to obtain a cross-section modified polyester fiber.
[0062] S2. Cross-section modified polyester fiber and cotton fiber are blended to form warp yarn and weft yarn, wherein the content of cross-section modified polyester fiber in the warp yarn is 55wt%, and the content of cotton fiber is 45wt%; the content of cross-section modified polyester fiber in the weft yarn is 76wt%, and the content of cotton fiber is 24wt%; then the warp yarn and the weft yarn are cross-woven to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth; the linear density of the warp yarn is 18tex, and the linear density of the weft yarn is 18tex. The specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 362 yarns / 10cm, and the weft yarn density is 328 yarns / 10cm;
[0063] S3. The cross-proof moisture-absorbing quick-drying functional fabric base fabric is immersed in the finishing liquid for double immersion and double rolling treatment, and the liquid carrying rate is 80%. Then, the fabric base fabric after the immersion and rolling treatment is baked, washed, and dried to obtain the cross-proof moisture-absorbing quick-drying functional fabric; the baking conditions are pre-baking at 95°C for 3min, then cooling to 65°C, and continuing to bake for 3min; the finishing liquid is obtained by uniformly mixing 15g carbon nanotubes, 68g blocked isocyanate cross-linking agent, 7g hydroxyethyl cellulose, and 1000g water.
[0064] Comparative Example 3
[0065] A method for preparing a cross-shaped anti-permeability, moisture-absorbing and quick-drying functional fabric is similar to that of Example 1, except that no modified carbon nanotubes are added to the finishing liquid, and specifically comprises the following steps:
[0066] S1. Disperse 150 parts of polyester fibers in 500 mL of water after plasma treatment. The plasma treatment process is to evacuate the plasma instrument and then introduce oxygen. The power is set to 180 W and the treatment time is 8 min. Add 24.8 g of epichlorohydrin and 58.6 g of carboxymethyl chitosan, heat and stir at 60 ° C for 2 h, and after the reaction is completed, filter, wash and dry the reaction product, and then spray it through a cross-shaped spinneret, and then stretch and wind it to obtain a cross-section modified polyester fiber.
[0067] S2. Cross-section modified polyester fiber and cotton fiber are blended to form warp yarn and weft yarn, wherein the content of cross-section modified polyester fiber in the warp yarn is 55wt%, and the content of cotton fiber is 45wt%; the content of cross-section modified polyester fiber in the weft yarn is 76wt%, and the content of cotton fiber is 24wt%; then the warp yarn and the weft yarn are cross-woven to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth; the linear density of the warp yarn is 18tex, and the linear density of the weft yarn is 18tex. The specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 362 yarns / 10cm, and the weft yarn density is 328 yarns / 10cm;
[0068] S3. The cross-proof moisture-absorbing and quick-drying functional fabric base fabric is immersed in the finishing liquid for double immersion and double rolling treatment, and the liquid carrying rate is 80%. Then, the fabric base fabric after the immersion and rolling treatment is baked, washed, and dried to obtain the cross-proof moisture-absorbing and quick-drying functional fabric; the baking conditions are pre-baking at 95°C for 3min, then cooling to 65°C, and continuing to bake for 3min; the finishing liquid is obtained by uniformly mixing 68g of blocked isocyanate cross-linking agent, 7g of hydroxyethyl cellulose, and 1000g of water.
[0069] Test Case
[0070] Flame retardant performance test: According to the test method of GB / T5454-1997 "Textile Combustion Performance Test Oxygen Index Method", the limiting oxygen index of the cross-shaped anti-permeability moisture absorption and quick-drying functional fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was measured using a FYH830 critical oxygen index tester;
[0071] Antistatic performance test: The cross-shaped anti-permeability moisture absorption and quick-drying functional fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were tested using the C method (charge surface density method) in the national standard GB / T12703-1991 "Textile Electrostatic Test Method";
[0072] Antibacterial performance test:
[0073] With reference to the simplified washing conditions and procedures of FZ / T73023-2006 "Antibacterial knitwear", the standard detergent concentration used is 2 g / L. The fabrics obtained in Examples 1-3 and Comparative Examples 1-3 were washed in a constant temperature oscillating water bath at 40°C for 5 min, and then washed with distilled water. This process was regarded as one wash. According to the above procedure, the lightweight warm and comfortable clothing fabrics were washed 100 times to test the antibacterial properties of the washed fabrics. Escherichia coli ATCC 8099 was used as the experimental strain. The antibacterial property test was based on GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method".
[0074] Wear resistance test: Cut five circular specimens with a diameter of 120 mm from the fabrics prepared in Examples 1-3 and Comparative Examples 1-3, respectively, and apply a 500 g weight hammer. After 200 turns of wear, the weight loss of the fabrics is tested, and the weight loss rate of the fabrics is calculated. The weight loss rate is calculated as W=(G1-G2) / G1;
[0075] Where W is the weight loss rate of the fabric, G1 is the weight of the fabric before abrasion, G2 is the weight of the fabric after abrasion, and the test results are averaged;
[0076] The test results are shown in Table 1:
[0077] Table 1 Test results of flame retardant and antistatic properties of fabrics
[0078]
[0079] It can be seen from the experimental results in Table 1 that the cross-shaped anti-permeability moisture-absorbing quick-drying functional fabric prepared by the present invention has excellent flame retardant, antistatic, antibacterial and wear-resistant properties.
[0080] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A method for preparing a cross-shaped anti-permeability, moisture-absorbing and quick-drying functional fabric, characterized in that: The steps include: S1, dispersing the polyester fiber treated with plasma in water, adding epichlorohydrin and carboxymethyl chitosan thereto, heating and stirring to react, after the reaction is completed, filtering, washing, and drying the reaction product, and then spraying it through a cross-shaped spinneret, and then stretching and winding it to spin a cross-section modified polyester fiber; S2, blending the cross-section modified polyester fiber and cotton fiber to form warp yarn and weft yarn, and then cross-weaving the warp yarn and weft yarn to obtain a cross-proof moisture-absorbing quick-drying functional fabric base cloth; S3, immersing the cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric base fabric in a finishing liquid for padding treatment, and then baking, washing, and drying the padding-treated fabric base fabric to obtain the cross-shaped anti-permeable moisture-absorbing quick-drying functional fabric; In step S3, the finishing liquid is obtained by uniformly mixing 1-2 parts of modified carbon nanotubes, 4-8 parts of blocked isocyanate crosslinking agent, 0.5-1 part of hydroxyethyl cellulose, and 80-120 parts of water; The preparation method of the modified carbon nanotubes is as follows: The carbon nanotubes are dispersed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, heated and stirred by ultrasonic treatment, cooled to room temperature, filtered, the solids are collected, washed with water until neutral, and dried to obtain pretreated carbon nanotubes; After the pretreated carbon nanotubes and the ethanol aqueous solution are evenly mixed, 3-aminopropyltriethoxysilane is added, heated to react, cooled, filtered and dried to obtain the amino carbon nanotubes; the amino carbon nanotubes, epichlorohydrin, melamine and sulfaguanidine are added to water, stirred and mixed evenly, sodium hydroxide is added, heated and stirred to react, after the reaction is completed, filtered, the solid matter is collected and dried to obtain the modified carbon nanotubes.
2. The preparation method according to claim 1, characterized in that: The plasma treatment conditions in step S1 are as follows: after the plasma instrument is evacuated, oxygen is introduced, the power is set to 150-200 W, and the treatment time is 5-10 min.
3. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of polyester fiber, epichlorohydrin and carboxymethyl chitosan is 10-20:2-3:4-8.
4. The preparation method according to claim 1, characterized in that: In the step S2, in the composition of the warp yarn, the content of the cross-section modified polyester fiber is 50-60wt%, and the content of the cotton fiber is 40-50wt%.
5. The preparation method according to claim 1, characterized in that: In the step S2, in the composition of the weft yarn, the content of the cross-section modified polyester fiber is 70-80wt%, and the content of the cotton fiber is 20-30wt%.
6. The preparation method according to claim 1, characterized in that: In the step S2, the linear density of the warp yarn is 15-20 tex, and the linear density of the weft yarn is 15-20 tex.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the amino carbon nanotubes, epichlorohydrin, melamine and sulfaguanidine is 5-6:3-5:4-6:2-3.
8. A cross-shaped moisture-absorbing and quick-drying functional fabric, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Moisture-absorbing and quick-drying fabric and preparation method thereof
CN114474890A
Flexible flame-retardant cable material and preparation method thereof
CN106084552A
Sweat-releasing and antibacterial fabric and preparation method thereof
CN112941696A
Antibacterial polyester composite fiber and preparation method thereof
CN117845614A